(New page: Let <math>\chi (w) = \pi \delta (w - 6) - \pi \delta (w - 3)</math>)
 
Line 1: Line 1:
Let <math>\chi (w) = \pi \delta (w - 6) - \pi \delta (w - 3)</math>
+
Let <font size = '4'><math>\chi (w) = \pi \delta (w - 6) - \pi \delta (w - 3)</math></font>

Revision as of 13:37, 8 October 2008

Let $ \chi (w) = \pi \delta (w - 6) - \pi \delta (w - 3) $

Alumni Liaison

Ph.D. on Applied Mathematics in Aug 2007. Involved on applications of image super-resolution to electron microscopy

Francisco Blanco-Silva